Cytochrome P4504A inhibitors attenuate the exaggerated natriuretic response to volume expansion in thyroidectomized rats. Issue 6 (11th June 2014) - Colombero, Cecilia; Venara, Marcela; Gonzalez, Daniel; Roman, Richard J.; Nowicki, Susana
Abstract Thyroidectomy augments the natriuretic response to volume expansion; however, the mechanism remains unknown. This study assessed the role of 20‐hydroxyeicosatetraenoic acid (20‐HETE) in the natriuretic response to an acute volume expansion in hypothyroid rats. Urine flow (1.9‐fold), sodium excretion (2.4‐fold), fractional sodium excretion (3.8‐fold), and distal delivery of sodium (4.1‐fold) increased to a greater extent in thyroidectomized rats (TX) than in sham‐operated controls (SHAM) following i.v. infusion of isotonic saline (5% body weight) over 60 min. This was associated with inhibition of both proximal and distal tubular reabsorption of sodium. Administration of two mechanistic and chemical dissimilar inhibitors of the synthesis of 20‐HETE, 1‐aminobenzotriazole (ABT), and N‐hydroxy‐N'‐(‐4‐butyl‐2‐methylphenyl)formamidine (HET0016) decreased the natriuretic response in TX rats. Glomerular filtration rate was lower in TX than in SHAM rats and was not altered by the CYP4A inhibitors. The expression, intrarenal distribution, and the formation of 20‐HETE and expoxygenase metabolites of arachidonic acid were similar in the cortex and medulla of SHAM and TX rats. These results suggest that CYP4A‐derived metabolites of arachidonic acid play an important role in the enhanced natriuretic response to volume expansion in hypothyroid rats even though TX did not alter the expression or activity of these enzymes.